A Statist Political Economy and High Demand for Education in South Korea - Kim, Ki Su (Education Policy Analysis Archives, 1999)
In the 1998 academic year, 84 percent of South Korea's high school "leavers" entered a university or college while almost all children went up to high schools. This is to say, South Korea is now moving into a new age of universal higher education. Even so, competition for university entrance remains intense. What is here interesting is South Koreans' unusually high demand for education. In this article, I criticize the existing cultural and socio-economic interpretations of the phenomenon. Instead, I explore a new interpretation by critically referring to the recent political economy debate on South Korea's state-society/market relationship. In my interpretation, the unusually high demand for education is largely due to the powerful South Korean state's losing flexibility in the management of its "developmental" policies. For this, I blame the traditional "personalist ethic" which still prevails as the